Penyuluhan Sanitasi Bersih dalam Upaya Mewujudkan Sustainable Development Goals (SDGs) di Kelurahan Serua Depok - Widiastutie, Sophiana; Juned, Mansur; Darmastuti, Shanti; Manurung, Steven Montesquieu; Shaliha, Shiella Najwa (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims is to increase the knowledge and awareness of community members regarding the importance of clean sanitation in an effort to realize Sustainable Development Goals (SDGs) in Kelurahan Serua, Bojongsari, Depok. The method of implementing this service uses counselling with partners is Tim Pokja Sehat Kelurahan Serua, Bojongsari, Depok. The evaluation instrument for this service uses Pre-test and Post-Test evaluations and is analyzed descriptively. The results of this service show that participants’ knowledge and awareness has increased regarding the importance of clean sanitation including waste management, clean water, healthy latrines, and correct waste management. So, it is hoped that the result of this service can have an impact on the realization of Sustainable Development Goals (SDGs).